ANALISIS STRATEGI PEMASARAN PADA USAHA KECIL MENENGAH (UKM) MAKANAN RINGAN ( Studi Penelitian UKM Snack Barokah di Kota Bima - Arsad Arsad; Sukardi Sukardi; Mukhlis Mukhlis (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
Small and medium enterprises (SMES) have a great role in national economic growth.To maintain the continuity of the activities of SMES in the middle of an existing business competition needed a proper marketing strategy management to achieve company goals. Factors that may affect the marketing strategy stems from internal factors and external factors. The object of this research is the company's Snack business form that is Snack barokah that have yet to implement a proper marketing strategy management to expand its business. This study aims to identify the factors that may affect and become elements of the marketing strategy as well as develop and recommend an appropriate marketing strategy to be applied This research use analyses QSPM (Quantitave Planing Strategy Matrix) to devise strategies that will be taken. The sample of this research taken from Parties within the company. Determination of samples as respondents using purposive sampling with a respondent's consideration that is has the ability and authority in formulating marketing strategies company. This research resulted in SME strategic alternatives and the priority order of Snack Barokah as follows: increase product quality by using a packaging machine, producing their own snacks, increasing quality of products to face competition, seeking additional capital to take advantage of a Government loan program, maintain price levels and improve the quality of flavour, vigorous business products promotion by utilizing electronic media facilities, increase promotion directly approach the way to expand the market whole salers consumer voice, delivers, and maintains good relations with suppliers